Identification of five different IGHV gene families in owl monkeys (Aotus nancymaae) (2005)
In order to characterize immunoglobulin heavy?chain variable (IGHV ) genes in Aotus nancymaae monkeys, different mRNAs encoded by five IGHV families in this non?human primate were molecularly analysed considering their paramount importance in antibody production in an immune response. This study reports gene products exhibiting 91% amino acid similarity with IGHV1, IGHV2, IGHV3, IGHV4 and IGHV7 human IGHV families. Our analyses suggest that the IGHV gene has several conserved characteristics in humans and A. nancymaae . Several amino acid residues that are highly conserved in all family members described in humans were also present in these families in A. nancymaae . Antibody diversity in these families has remained the same since divergence of both species. Our study continues to provide evidence supporting the use of A. nancymaae monkey as an animal model for studying antibody response.